2011
DOI: 10.1007/s12079-011-0143-1
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cytochrome P4501A by protein kinase C: the role of heat shock protein70

Abstract: Carbofuran is a pesticide, which is used throughout the world as a nematicide and an acaricide. This pesticide integrates into living organisms through aquatic ecosystem. In earlier report, we had demonstrated that cytochrome P4501A was induced in cultured catfish hepatocytes in response to carbofuran, which might be responsible for the detoxification of this pesticide. As the underlying signaling mechanism associated with induction and regulation of cytochrome P4501A has not yet been well defined, we therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…It has been well established that p38 can be activated by osteonectin in the studies of heat shock proteins in malignant tumors (Alam, Schultz, Golembieski, Poisson, & Rempel, ; McClung et al, ); although the mechanisms in mineralization has not been reported, previous research works have presented plausible methods for osteonectin to activate p38. Osteonectin regulates the extracellular matrix assembly, activates matrix metalloproteinases, and is related to the signal conduction of the integrins (Arnold & Brekken, ; Funk & Sage, ; Tremble, Lane, Sage, & Werb, ), metalloproteinases and integrins have been demonstrated to play a critical role in mechanical stress‐induced p38 MAPK activation (Aikawa et al, ; Kasper et al, ; Yi, Liu, Fong, Zhang, & Yang, ); furthermore osteonectin can alter the configuration of collagen, which contains receptors such as discoidin receptor 2 that can activate P38 (Ge et al, ); in addition, MKK3 and MKK6 are the upstream protein kinases responsible for p38 activation (Dérijard et al, ; Remy et al, ), the MKK3/6‐p38 pathway has been suggested as the main mediator of TGF‐b‐activated kinase 1 in osteoblasts (Greenblatt et al, ), while osteonectin also has a reciprocal regulatory feedback loop with TGFβ (Francki et al, ; Kang, Oh, Kang, & Rhee, ). Multiple proteins and signaling pathways have cross‐influences, the precise mechanism of these signaling events triggered by osteonectin needs to be examined further.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well established that p38 can be activated by osteonectin in the studies of heat shock proteins in malignant tumors (Alam, Schultz, Golembieski, Poisson, & Rempel, ; McClung et al, ); although the mechanisms in mineralization has not been reported, previous research works have presented plausible methods for osteonectin to activate p38. Osteonectin regulates the extracellular matrix assembly, activates matrix metalloproteinases, and is related to the signal conduction of the integrins (Arnold & Brekken, ; Funk & Sage, ; Tremble, Lane, Sage, & Werb, ), metalloproteinases and integrins have been demonstrated to play a critical role in mechanical stress‐induced p38 MAPK activation (Aikawa et al, ; Kasper et al, ; Yi, Liu, Fong, Zhang, & Yang, ); furthermore osteonectin can alter the configuration of collagen, which contains receptors such as discoidin receptor 2 that can activate P38 (Ge et al, ); in addition, MKK3 and MKK6 are the upstream protein kinases responsible for p38 activation (Dérijard et al, ; Remy et al, ), the MKK3/6‐p38 pathway has been suggested as the main mediator of TGF‐b‐activated kinase 1 in osteoblasts (Greenblatt et al, ), while osteonectin also has a reciprocal regulatory feedback loop with TGFβ (Francki et al, ; Kang, Oh, Kang, & Rhee, ). Multiple proteins and signaling pathways have cross‐influences, the precise mechanism of these signaling events triggered by osteonectin needs to be examined further.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we observed that P4501A was induced by de novo synthesis to combat the presence of aromatic hydrocarbon compounds, such as, carbofuran or β-napthoflavone in the hepatocytes of catfish livers as evidenced by an increase in enzymatic activity of EROD [22]. Carbofuran induced the phospholipid in the membrane of hepatocytes which might be involved in activating a signaling cascade, including protein kinase C (PKC) or heat shock protein 70 (HSP70) [38]. The role of phospholipid in the activation of enzymatic activity of membrane-bound protein, including cytochrome P450 has been studied by many investigators [7], [8], [10], [39], [40], [41].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, exposure to carbofuran caused decrease in EROD activity when compared to controls. The decrease of CYP1A catalytic activity might be due to the inhibition of its mRNA expression by carbofuran [29]. Many xenobiotic compounds, such as heavy metals at high concentrations, have shown effects of inhibition and/ or decrease of liver microsomal cytochromes P4501A (CYP1A) activity in fish [30].…”
Section: Discussionmentioning
confidence: 99%